Life quality of patients with inflammatory bowel disease: integrative review (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objective: To identify the scientific production about life quality (LQ) of people with inflammatory bowel disease (IBD) in the period from 2012 to 2016. Method: This is an integrative literature review realized in the Scientific Electronic Library Online database (SciELO) in which the articles published freely in Portuguese and/or English published in the last five years and with the descriptors IBD and LQ were used as inclusion criterion. Results: Eight articles were identified and, after partial reading, four were selected, three of which were published in 2015 and one in 2014. The discoveries are in line with other studies that show that vitamin D and ferric carboxymaltose may improve the LQ of patients with IBD. It was also found that women and Crohn’s disease predominate among people with IBD, and that LQ is usually negatively affected in these patients, with repeUCssions on their personal and professional relationships. Conclusion: There was a shortage of literature on LQ of people with IBD, mainly in studies conducted in Brazil, since only one clinical study was found.